"MODERN COMMENTARIES ON SOCIOLINGUISTIC RESEARCH" (Scientific journal of the Fergana State University, 2024)
In the advancement of international linguistics, sociolinguistics holds a special place, studying the relationships between language, society, and culture. Additionally, in the modern world, the formation and expression of various sociocultural concepts are crucial aspects. One such concept pertains to phenomena related to the concepts of "gender" and "age," which acquire particular significance for sociolinguistic and phraseological studies. Investigating sociolinguistic units associated with the expression of "gender" and "age," as well as their usage characteristics in various cultural contexts, deeper understanding and the foundation for cultural communication modules are established. In recent years, sociolinguistic research focusing on examining the social and linguistic relationships between gender and age has become an important task for developing intercultural communication. Analyzing the impact of linguistic expressions, stereotypes, and customs on gender and age aspects of social consciousness helps to understand the mutual influence of language and social phenomena and contributes to shaping individuality based on gender and age in different cultures and societies.